Detection of anti-HspX antibodies and HspX protein in patient sera for the identification of recent latent infection by Mycobacterium tuberculosis - Izzo, Angelo A.; Castro Garza, Jorge Enrique; García Jacobo, Paola Janeth; Rivera Morales, Lydia Guadalupe; Quinn, Frederick D.; Barber, James; Karls, Russell; Haas, Debra; Helms, Shelly; Gupta, Tuhina; Blumberg, Henry; Tapia, Jane; et al. (2017)
Abstract Mycobacterium tuberculosis is a pathogen causing tuberculosis (TB) a spectrum of disease including acute and asymptomatic latent stages. Identifying and treating latently-infected patients constitutes one of the most important impediments to TB control efforts. Those individuals can remain undiagnosed for decades serving as potential reservoirs for disease reactivation. Tests for the accurate diagnosis of latent infection currently are unavailable. HspX protein (α-crystallin), encoded by Rv2031c gene, is produced in vitro by M. tuberculosis during stationary growth phase and hypoxic or acidic culture conditions. In this study, using standard, and Luminex xMAP® bead capture ELISA, respectively, we report on detection of anti-HspX IgG and IgM antibodies and HspX protein in sera from acute and latent TB patients. For the antibody screen, levels of IgG and IgM antibodies were similar between non-infected and active TB patients; however, individuals classified into the group with latent TB showed higher values of anti-HspX IgM (p = 0.003) compared to active TB patients. Using the bead capture antigen detection assay, HspX protein was detected in sera from 56.5% of putative latent cases (p< 0.050) compared to the background median with an average of 9,900 pg/ml and a range of 1,000 to 36,000 pg/ml. Thus, presence of anti-HspX IgM antibodies and HspX protein in sera may be markers of latent TB.